1,5-Bis[(E)-1-(2-hydroxyphenyl)ethylidene]thiocarbonohydrazide monohydrate - Abu Affan, M.; Chee, D.N.A.; Ahmad, F.B.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C17H18N4O2S center dot H2O, the thiourea derivative is almost planar, with an r.m.s. deviation for the non-H atoms of 0.057 angstrom. The hydroxyl groups lie to the same side of the molecule as the thione S atom, a conformation that allows the formation of intramolecular O-H center dot center dot center dot S and O-H center dot center dot center dot N hydrogen bonds. In the crystal structure, the thiourea and water molecules self-assemble into a two-dimensional array by a combination of O-(water)-H center dot center dot center dot O-hydroxyl, N-H center dot center dot center dot O-water and O-water-H center dot center dot center dot S hydrogen bonds and C-H center dot center dot center dot pi interactions.